2017
DOI: 10.1016/s1474-4422(16)30358-1
|View full text |Cite
|
Sign up to set email alerts
|

Pain in amyotrophic lateral sclerosis

Abstract: Pain is a largely neglected symptom in amyotrophic lateral sclerosis (ALS) although reported in a majority of patients. It occurs at all stages of the disease and can be an onset symptom preceding motor dysfunction. Pain is correlated with a deterioration of the patient's quality of life and increased depression. In the later stages of ALS, the pain severity can be such as to require increasing use of sedative-analgesic drugs and is among the events predicting clinical deterioration and death. The site of pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
119
0
19

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(139 citation statements)
references
References 111 publications
(214 reference statements)
1
119
0
19
Order By: Relevance
“…In fact both studies found no patients with neuropathic pain, which is intriguing since up to 7% of the general population is considered to have pain of neuropathic characteristics (Bouhassira et al., ). The present study does not allow drawing further conclusions on this topic, but since this was one of the few studies where the diagnosis of neuropathic pain was based on clinical assessment based on formal definition, it suggests this pain syndrome may not be a clinically significant pain syndrome in MND (Chiò et al., ) or may be neuropathic pain was controlled and remained subclinical due to the use of psychotropics already prescribed to these patients to control other symptoms such as excessive drooling.…”
Section: Discussionmentioning
confidence: 77%
“…In fact both studies found no patients with neuropathic pain, which is intriguing since up to 7% of the general population is considered to have pain of neuropathic characteristics (Bouhassira et al., ). The present study does not allow drawing further conclusions on this topic, but since this was one of the few studies where the diagnosis of neuropathic pain was based on clinical assessment based on formal definition, it suggests this pain syndrome may not be a clinically significant pain syndrome in MND (Chiò et al., ) or may be neuropathic pain was controlled and remained subclinical due to the use of psychotropics already prescribed to these patients to control other symptoms such as excessive drooling.…”
Section: Discussionmentioning
confidence: 77%
“…Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease primarily affecting the motor system and characterized by progressive degeneration of the motor neurons [1,2]. The prevalence of ALS cases is estimated to increase by almost one third from 2015 to 2040 [3].…”
Section: Introductionmentioning
confidence: 99%
“…Not all patients have the complete phenotype of FSHD, and clinical severity varies widely among patients, including great variability of weakness within families. Chronic pain is a significant problem in different neuromuscular conditions, such as limb‐girdle muscular dystrophy 1C, myotonic dystrophies, and FSHD; in some cases, pain may even be the first disease manifestation . Reports about pain in FSHD‐phenotype patients predate the development of genetic testing.…”
mentioning
confidence: 99%